2014
DOI: 10.1155/2014/571065
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Bone and Body Mass in Young Male Rats Exposed to Lead

Abstract: The aim of this study was to see whether there would be differences in whole blood versus tibia lead concentrations over time in growing rats prenatally. Lead was given in the drinking water at 30 mg/L from the time the dams were pregnant until offspring was 28- or 60-day-old. Concentrations of lead were measured in whole blood and in tibia after 28 (28D) and 60 days (60D) in control (C) and in lead-exposed animals (Pb). Lead measurements were made by GF-AAS. There was no significant difference (P > 0.05) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“… 37 BTM has been used for the assessment of early stage osteoporosis. 38 Animal studies of lead intoxication have reported higher lead accumulation in osteoblast cultures, 39 decreased bone density, 40 delayed fracture healing, 21 and increased BTMs 41 . The changes of bone formation and bone resorption markers lead to osteocalcin-dependent osteopenia.…”
Section: Discussionmentioning
confidence: 99%
“… 37 BTM has been used for the assessment of early stage osteoporosis. 38 Animal studies of lead intoxication have reported higher lead accumulation in osteoblast cultures, 39 decreased bone density, 40 delayed fracture healing, 21 and increased BTMs 41 . The changes of bone formation and bone resorption markers lead to osteocalcin-dependent osteopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Higher amounts of lead (at least 5 times more) have been found in the bone of experimental animals, even in situations where whole blood lead levels remained unchanged (Tocchini de Figueiredo et al, 2014). Based on their findings, these workers reaffirmed the importance of using bone concentration of Pb as a more reliable biomarker for exposure rather than whole blood lead concentrations.…”
Section: Biochemical Analysesmentioning
confidence: 92%
“…The lack of significant difference between blood lead concentrations for control group and Pb-exposed groups could be as a result of short period of lead intoxication (7 days of intoxication prior to 8 days of treatment of relevant groups with ORK and ascorbic acid respectively). Studies using longer exposure periods have reported significant variations in blood lead levels between control and Pb-exposed groups (Fioresi et al, 2014;Tocchini de Figueiredo et al, 2014). Nevertheless, the highest mean blood lead concentration of 69.2 ± 0.11 μg dL -1 was detected for Group B (Pb treated, no ORK and no AA); this amount was slightly reduced on treatment with both ORK and ascorbic acid (see Table 1).…”
Section: Biochemical Analysesmentioning
confidence: 95%
“…Tubes containing the whole blood were centrifuged (800 × g , 6 min) to obtain serum 42,43 . Syringes and needles were previously decontaminated in nitric acid 3% 44 .…”
Section: Methodsmentioning
confidence: 99%
“…To perform the analytical test a bi-distillated acid was diluted with deionized water ultrapure to reach 3% of acid on solution. Bone was dried in Chapel of laminar flow, to prevent the deposition of dust 44 . All this was done to avoid contamination of specimens.…”
Section: Methodsmentioning
confidence: 99%